Kewenangan Penangkapan oleh BNN dan Polri Terhadap Pelaku Tindak Pidana Narkotika di Tinjau dari Perspektif Hak Asasi Manusia (HAM) - Ronaldo Ragowino Bira; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2022)
The eradication of narcotics crime is very necessary so that it involves the police and BNN as stated in the mandate of Law No. 35 of 2009 concerning Narcotics. The method used in this paper is a qualitative legal material management method that uses a normative assessment, which is after the primary and secondary legal materials are collected, the presentation is carried out descriptively and systematically. The authority of BNN investigators and Polri investigators in investigating Narcotics crime has a different legal basis related to the period of arrest of narcotics criminals so that this causes human rights violations regarding the arrest period used by BNN and Polri investigators, resulting in the absence of legal certainty and Equal treatment before the law. The laws and regulations are expected to provide legal certainty and for BNN and Polri investigators to be more observant in carrying out their duties and responsibilities so as not to harm others and create legal certainty for the entire community.